Resistance Profile of Osimertinib in Pre-treated Patients With EGFR T790M-Mutated Non-small Cell Lung Cancer - Fernandes, Maria Gabriela O.; Sousa, Catarina; Jacob, Maria; Almeida, Leonor; Santos, Vanessa; Araújo, David; Novais Bastos, Hélder; Magalhães, Adriana; Cirnes, Luís; Moura, Conceição Souto; Queiroga, Henrique; Cruz-Martins, Natália; et al. (Frontiers in Oncology, 2021)
Background: Osimertinib efficacy in pre-treated patients with EGFR T790M-mutated non-small cell lung cancer (NSCLC) has been demonstrated in clinical trials, but real-world data, particularly regarding resistance profile, remains limited. Methods: A single-center retrospective analysis of EGFR T790M-mutated NSCLC patients, treated with osimertinib was performed. Clinical outcomes and molecular results from re-biopsies at the time of osimertinib progression were analyzed. Results: Twenty-one patients with stage IV adenocarcinoma were included (median 69 years; 57.1% female; 85.7% never-smokers; 23.8% ECOG performance status (PS) ≥2). Osimertinib was given as 2nd line in 61.9% of patients, and in 38.1% as 3rd line or more. Best ORR and DCR was 52.7% and 89.5%, respectively. Median PFS and OS were 13.4 (95% CI: 8.0-18.9) and 26.4 (95% IC: 8.9-43.8) months, respectively. At the time of analysis, 10 patients had tumor progression (47.6%). T790M loss occurred in 50%, being associated with earlier progression (median PFS 8.1 vs. 21.4 months, p=0.011). Diverse molecular alterations were identified as associated with resistance mechanisms to osimertinib, including C797S mutation (n=1), PIK3CA mutation (n=2), MET amplification (n=1), CTNNB1 mutation (n=1) and DCTN1-ALK fusion (n=1). Histological transformation into small cell carcinoma occurred in one patient. Conclusions: This real-world life study confirmed that both osimertinib efficacy and tolerability in pre-treated patients with EGFR T790M-mutated NSCLC is in line with clinical trials results. Re-biopsy at the time of disease progression is extremely important to understand the underlying resistance mechanisms and to guide treatment strategies.